Latest eco-friendly approaches for pesticides decontamination using microorganisms and consortia microalgae: A comprehensive insights, challenges, and perspectives. (December 2022) - Sheng, Yequan; Benmati, Mahbouba; Guendouzi, Salma; Benmati, Hadjer; Yuan, Yan; Song, Junlong; Xia, Changlei; Berkani, Mohammed
Abstract: Pesticides are chemical compounds that are considered toxic to many organisms, including humans. Their elimination from polluted sites attracted the attention of Scientifics in the last decade; Among the various methods used to decontaminate pesticides from the environment, the microbial-algae consortium is a promising bioremediation technology, which implies several advantages as an eco-friendly process that generate biomass produced that could be valorized in the form of bioenergy, In this review, we will discuss the latest eco-friendly approaches using microorganisms to remediate sites contaminated by pesticides, and shows the ability of microbial, algae and their consortium to remove pesticides and the role of different enzymes in degradation processes. Graphical abstract: Image 1 Highlights: Pesticides decontamination using microorganisms and microalgae was reviewed. High toxicity and persistence of pesticides are a major concern. Microbial-algae consortium is an eco-friendly approach. Microbial-algae consortium is a promising bioremediation technology. More in-depth studies need to be further developed for field application.